Validation of predictive equations for aerobic fitness in young healthy male students of the University of Ibadan - Johnson Babajide Oduyomi; Adesoji Fasanmade (Bulletin of Faculty of Physical Therapy)
Abstract Background Maximum oxygen consumption is a measure of an individual’s cardiorespiratory fitness which is a singular predictor of an array of diseases. Several exercise and non-exercise assessments are frequently compared to know which method(s) provide the most accurate estimation of aerobic capacity due to difficulties in using the direct method. There is a need to know if an estimation method is the right fit for a population without huge overestimation or underestimation due to ethnical variation. This study was undertaken to assess the estimations of the cardiorespiratory fitness of healthy African males by the submaximal exercise-based and the non-exercise-based equations in undergraduate students of the University of Ibadan, Nigeria. Results VO2 was significantly higher in the undergraduate students of the University of Ibadan in all the equations used (44.38 ± 39.07, 62.46 ± 27.61, 44.38 ± 39.07, 62.46 ± 27.61, 46.37 ± 3.31, 46.16 ± 3.64, 47.08 ± 3.19). The two submaximal exercises compared using the Bland–Altman Plot showed a high degree of agreement, further linear regression performed showed no proportional bias on the distribution of data around the mean difference line (p > 0.05). Cross-validation using the Bland–Altman plot and linear regression for the five non–exercise predicted equations with the YMCA submaximal exercise test and Bruce submaximal exercise test all showed a significance difference of (P < 0.05) showed that data from all the methods provided proportional bias on the distribution of data around the mean difference line. Conclusion This study asserts that caution should be taken when using a non-exercise equation to predict VO2 in the African population. It is therefore recommended to carry out various assessment methods of VO2 estimation in a wider population using various protocols, and also develop a predictive equation for VO2 specific to the African population.